(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The most significant betrayals that occurred during World War II, their causes, consequences and historical context are analyzed. Information is provided about the defection of General Vlasov and his army to the German side during the war.